Flavonoids as Molecules With Anti-Zika virus Activity - Cataneo, Allan Henrique Depieri; Ávila, Eloah Pereira; Mendes, Larissa Albuquerque de Oliveira; de Oliveira, Viviane Guedes; Ferraz, Camila Rodrigues; de Almeida, Mauro Vieira; Frabasile, Sandra; Duarte dos Santos, Claudia Nunes; Verri, Waldiceu Aparecido; Bordignon, Juliano; Wowk, Pryscilla Fanini (Frontiers in Microbiology, 2021)
Zika virus (ZIKV) is an arthropod-born virus that is mainly transmitted to humans by mosquitoes of the genus Aedes spp. Since its first isolation in 1947, only a few human cases had been described until large outbreaks occurred on Yap Island (2007), French Polynesia (2013), and Brazil (2015). Most ZIKV-infected individuals are asymptomatic or present with a self-limiting disease and nonspecific symptoms such as fever, myalgia, and headache. However, in French Polynesia and Brazil, ZIKV outbreaks led to the diagnosis of congenital malformations and microcephaly in newborns and Guillain-Barré syndrome in adults. These new clinical presentations raised concern from public health authorities and highlighted the need for anti-Zika treatments and vaccines to control the neurological damage caused by the virus. Despite many efforts in the search for an effective treatment, neither vaccines nor antiviral drugs have become available to control ZIKV infection and/or replication. Flavonoids, a class of natural compounds that are well known for possessing several biological properties, have shown activity against different viruses. Additionally, the use of flavonoids in some countries as food supplements indicates that these molecules are nontoxic to humans. Thus, here we summarize knowledge on the use of flavonoids as a source of anti-ZIKV molecules and discus the gaps and challenges in this area before these compounds can be considered for further preclinical and clinical trials.